CHATBOT PROTOTYPE TRAINING USING DEEP LEARNING METHODS FOR TOURISM IN NORTH SUMATRA - Fibriasari, Hesti; Putri, Tansa Trisna Astono; Widiastuti, Uyuni (Universitas Negeri Medan, 2024)
Tourism is one of the foreign exchange industry that has significant potential for expansion. One notable province is North Sumatra, which boasts a plethora of captivating tourism destinations. Advertising and insufficient management systems for tourism information are hindering the expansion of the tourism business. The younger generation lacks a significant comprehension of artificial intelligence and its utilization in Chatbots and support services. A Chatbot is a program designed to engage in conversations on your behalf. Consequently, the design and deployment of deep-learning Chatbots necessitate teaching. This non-profit initiative aimed to tackle the issue by providing direction, examples, and practical training on tourist Chatbot prototypes specifically from North Sumatra. The PKM curriculum offers teaching in marketing methods, specifically focusing on tourist information management systems. 2) Education on the core concepts of artificial intelligence, specifically focusing on Chatbots. 3) Training in deep learning for constructing Chatbots; 4) Training in using the Chatbot application. The purpose of this activity is to increase public knowledge and usage of Chatbot applications for obtaining information about tourism destinations in the province of North Sumatra, in order to raise awareness among tourists.